Optically Active Nanomaterials for Bioimaging and Targeted Therapy - Yang, Yu; Wang, Li; Wan, Bin; Gu, Yuxin; Li, Xinxin (Frontiers in Bioengineering and Biotechnology, 2019)
Non-invasive tracking for monitoring the selective delivery and transplantation of biotargeted agents in vivo has been employed as one of the most effective tools in the field of nanomedicine. Different nanoprobes have been developed and applied to bioimaging tissues and the treatment of diseases ranging from inflammatory and cardiovascular diseases to cancer. Herein, we will review the recent advances in the development of optics-responsive nanomaterials, including organic and inorganic nanoparticles, for multimodal bioimaging and targeted therapy. The main focus is placed on nanoprobe fabrication, mechanistic illustrations, and diagnostic, or therapeutical applications. These nanomedicine strategies have promoted a better understanding of the biological events underlying diverse disease etiologies, thereby facilitating diagnosis, illness evaluation, therapeutic effect, and drug discovery.